(untitled) (Latakia University Journal -Engineering Sciences Series, 2020)
. Performance improvement in Construction companies is a complex task, which requires great effort and care. The research aims to analyze the status of work at the general company for building and construction, in order to determine the available management problems and then determine the priorities that will be areas of possible improvement of the performance of the company. There used three tools to asses inputs ,processes and outputs , The result of evaluating the maturity (inputs) of project management showed weakness in performance as The rate of project management maturity reached 2.3 out of 5. Quality indicators (outputs) , where rates were less than the average, were identified, as it was the results of questionnaire of measuring customer satisfaction for a sample of projects implemented by the company and the mean of customer satisfaction was 2.73 out of 5. Finally main processes of the company were drown and then the “FMEA " was used to identify the processes which face trouble which were 41 process. As a result of this comprehensive analysis the priority areas and procedures for the performance improvement were proposed.